AUTONOMOUS LEARNING AND COMPREHENSION OF DIGITAL TEXTS OF COMMUNICATION STUDENTS - Campos-Pérez, Rosalvina (2023)
The objective of this research was to determine the relationship between autonomous learning and the comprehension of digital texts in Communication students from three Peruvian universities. The research was of correlational level and non-experimental design. The technique used was the survey and two questionnaires were applied using Microsoft Forms. The universe was constituted by the undergraduate students enrolled in 2021 in two national universities and a private one. A sample was used for convenience. 109 students from the Schools of Communication of the Federico Villarreal National University (Lima), National University of Piura (Piura,) and the Santo Toribio of Mogrovejo University (Chiclayo) participated. The critical level of digital text comprehension in relation to autonomous learning indicates a slight improvement in comparison to the other levels in terms of correlation; however, it is significant at a confidence level of 95%. Keywords: autonomous learning - comprehension of digital texts - intrinsic motivation - strategies